Shear Strength Parameters of Cement Stabilized Amorphous Peat of Various Water Additive Ratios at Different Natural Moisture Contents under Consolidated Undrained Triaxial Test - Rahmi, A.; Taib, S.N.L.; Sahdi, F.; Mapplati, M.J.; Ghani, M.K. (Blue Eyes Intelligence Engineering & Sciences Publication, 2020)
Peat is a problematic soil which has a low shear strength characteristic. Addition of cement can improve the properties and strength of peat soil. This paper presents the findings of the shear characteristic of cement stabilized amorphous peat under consolidated undrained (CU) triaxial test. Three different natural moisture contents of peat which are 1210%, 803% and 380%, were stabilized using cement with water to additive (W/A) ratio of 2.0 and 3.0. CU triaxial test was conducted to the specimens after cured for 90 days. The shear parameters and characteristics were investigated towards the change of W/A ratio of the samples with different moisture contents. The result shows that the stabilized peat specimens exhibited ductile behavior and were sensitive to the over consolidation. The total and effective cohesion (ccu, c′) of the stabilized peat were found to be greater at W/A ratio of 2.0 compared to W/A ratio of 3.0, and greater at lower initial moisture content specimens. The total and effective friction angles (φcu, φ′) are ranged from 14o to 27o and 36o to 47o consecutively and found to be increased upon the increase of W/A ratio except for the specimens with moisture content 1210% and 803% in term of total friction angle.